Developing the Writing Skill of the University of Technology' Students by using Clustering Technique - Abed, Ban Kadhim (Al-Adab Journal, 2019)
The difficulties in writing are considered one of the most significant problems that have an effect on non-native English speakers. This study aims at developing the writing skills by using clustering technique to the University of Technology' students, then making a comparison between students' performance in writing in a per and post-test. A pre-test was made to the students to know their level in writing an essay then a course of study in teaching writing by using clustering technique was delivered to the students then a post-test is taken by students. The study aims at showing the influence using clustering technique in students' performance in writing. So the results have shown that there is a great development in students’ performance in writing after their involvement in the course